Investigasi Potensi Warisan Arsitektur untuk Pariwisata: Studi Kasus Hotel Salak Kota Bogor - Hastjarjo Hastjarjo; Agus Prihantono; Nisa Rahmaniyah Utami (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
In the past, in front of Bogor station there was a horse carriage from hotels to pick up guests who came. There were three luxury hotels that used to exist in Bogor; (1) Hotel Du Chemin De Fer on Jalan Capt Muslihat, now the Bogor Police Station, (2) Hotel Bellevue at the turn of Jalan Ir H Juanda, now Mall BTM, and (3) Hotel Dibbets (1856), later changed its name to NV American Hotel (1913) and Bellevue Dibbets (1932), still operating as Hotel Salak and are the only legendary hotels in Buitenzorg. This paper aims to support the preservation of architectural heritage in the city of Bogor, especially Hotel Salak as an inseparable part of the history of the city of Bogor by synergizing the study of conservation potential and the economic value of architectural heritage tourism (AHT). The methodology of this research is a case study of single identification of Hotel Salak Bogor as a bounded system of AHT. AHT stakeholders; The Tourism Office, Hotel Operators, and Academics must work together in conservation and tourism development, because AHT = conservation + tourism potential